Asymmetric Policy Concept for Border Areas Development: Issues and Challenges - Hanief Adrian; Rohmad Supriyadi; Diah Lenggogeni (Department of Urban and Regional Planning, Universitas Diponegoro, 2017)
Since the enactment of Law No. 23 Year 2014 about Local Government, there is a mechanism shift in service delivery from the local government to central government, especially related to infrastructure management in border areas. This shift has reversed the policy of decentralized service delivery mechanism to centralized one. This policy has confused the local governments in adjusting their policies to the central government policies. Thus, an asymmetric policy needs to be implemented in order to accelerate border areas development. This paper intends to propose the alternative options in dealing with the new policy and to design a better way how the central government may intervene asymmetrically the sub-national governments in accelerating development and service delivery mechanism in border areas. The descriptive analysis is used as the main method for this paper.